Gangliosides as regulators of cell signaling: ganglioside‐protein interactions or ganglioside‐driven membrane organization?. (28th January 2013) - Sonnino, Sandro; Mauri, Laura; Ciampa, Maria G.; Prinetti, Alessandro
<x xml:space="preserve">Abstract</x> Read the full article 'Involvement of gangliosides in the process of Cbp/PAG phosphorylation by Lyn in developing cerebellar growth cones' on doi: 10.1111/jnc.12040.